Examining the levels of awareness, anxiety, and hope regarding global climate change among university students participating in activities at youth offices - Yildiz, Metin (Frontiers in Psychology, 2025)
BackgroundClimate change is one of the most significant issues of today. This study aims to investigate climate change awareness, anxiety, and hope levels among university students who participate in activities at youth offices and examine the relationship between them.MethodsThe study population consisted of student members who were actively engaged in Youth Offices located within four public universities in the Eastern Anatolia Region of Türkiye. The study sample includes 881 volunteer participants, consisting of 345 (39.2%) male and 536 (60.8%) female students. The data were analyzed employing IBM SPSS 25. Statistical analyses included the independent samples t-test, one-way ANOVA, Tukey’s post-hoc test, and Pearson’s correlation coefficient.ResultsThe results indicate that university students have moderate levels of climate change awareness, anxiety, and hope. A positive correlation was observed, wherein higher awareness levels were associated with increased anxiety and hope. Male students demonstrated higher awareness and anxiety levels than female students. Among participants, students from 1. University exhibited the highest levels of climate change awareness, anxiety, and hope. Additionally, graduate students and individuals living in rural areas showed higher awareness and anxiety levels, whereas individuals with better economic conditions exhibited lower anxiety and hope levels.ConclusionGiven these results, it is recommended that universities develop and implement educational programs to enhance climate change awareness and extend these initiatives across campuses.